Improving Student's Critical Thinking Ability Through The Jigsaw Learning Model - Zahratul Azizah; Elyusra Ulfah (Universitas Negeri Padang, 2021)
Problems that are often encountered in learning activities include students having difficulty expressing ideas and opinions related to lecture material, when their discussions are more fixated on explaining the reading sources they get either through books or through other electronic media without being able to develop and explain rationally, analysis, as well as critical of the source of the reading. In terms of lecturers as educators, in providing learning to students, on average, they still use conventional patterns, namely the lecture model where students only act as recipients of information from the lecturers. All of this will certainly lead to the development of students' critical thinking skills during lectures. The ability to think critically, of course cannot be obtained just like that without a process in education, and not everyone can easily get it. This study aims to determine how to improve students' thinking skills through a jigsaw learning model. The method used in this research is class action with two cycles. The results showed that there was an increase in students' critical thinking skills after using the jigsaw learning model in learning activities.Key words : Learning, Model of Jigsaw Learning, Critical Thinking Ability